Characterization of Concrete with Rice Husk Ash (RHA) Based on Density, Porosity, and Sound Absorption - Nurul Azmi Ridha; Rahmaniah Rahmaniah (Jurnal Pijar MIPA, 2026)
This study addresses the growing need for sustainable construction materials by utilizing agricultural waste as a value-added resource. This study investigates the effect of incorporating rice husk ash (RHA) with different particle sizes on the physical and acoustic properties of concrete blocks. Rice husk ash is an agricultural waste product rich in silica, offering significant potential as a supplementary construction material while contributing to sustainable waste management. Therefore, this research aims to analyze the influence of RHA particle size on the porosity, density, and sound absorption characteristics of concrete blocks. Concrete block samples were prepared using mixtures without RHA as a control and mixtures containing RHA with particle sizes sieved at 0.1 cm, 0.2 cm, and 0.3 cm. Prior to mixing, the rice husk ash was thermally treated in a furnace at 500 °C to obtain stable ash with appropriate mineral composition. Mineralogical analysis confirmed that the ash was predominantly composed of silica (Si). Porosity was determined based on the ratio of void volume to total volume, density was calculated from mass per unit volume, and sound absorption performance was evaluated using the sound absorption coefficient (α). The results show that RHA particle size significantly influences the properties of concrete blocks. The lowest porosity (9.38%) and the highest sound absorption coefficient (α ≈ 0.25) were achieved by the sample with a particle size of 0.1 cm, indicating improved acoustic performance. Meanwhile, the highest density of 663.33 kg/m³ was obtained from the 0.2 cm sample. These findings demonstrate that finer RHA particles enhance both the structural compactness and acoustic properties of concrete blocks, supporting their application as environmentally friendly construction materials.